2019
DOI: 10.1002/aelm.201800835
|View full text |Cite
|
Sign up to set email alerts
|

Switching Kinetics Control of W‐Based ReRAM Cells in Transient Operation by Interface Engineering

Abstract: Tungsten (W) is one of the most promising materials to be used in resistive random‐access memory electrodes due to its low work function and compatibility with semiconductors, which raises the possibility of device integration, scalability, and low power consumption. However, W has multiple oxidation states that affect device reliability, due to the formation of semistable oxides at the switching interface. W chemical interaction is modulated through the insertion of Al2O3 or Ti interfacial layers. The time‐de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…[20,21] Huge randomness similar to the traditional metal-oxide-based memristor is found when amorphous PdSeO x is used as the switching medium (24% and −15.5% for set and reset voltage variations, respectively), as shown in Figure 3a-IV. [8][9][10] The impact of ozone treatment time on the switching behavior is further investigated, as shown in Figure S12 (Supporting Information). It is found that the variations in set and reset voltages are increased with longer treatment after the PdSeO x /PdSe 2 heterostructure is formed, showing a strong dependence on the treatment duration.…”
Section: Resistive Switching Mechanismmentioning
confidence: 99%
See 3 more Smart Citations
“…[20,21] Huge randomness similar to the traditional metal-oxide-based memristor is found when amorphous PdSeO x is used as the switching medium (24% and −15.5% for set and reset voltage variations, respectively), as shown in Figure 3a-IV. [8][9][10] The impact of ozone treatment time on the switching behavior is further investigated, as shown in Figure S12 (Supporting Information). It is found that the variations in set and reset voltages are increased with longer treatment after the PdSeO x /PdSe 2 heterostructure is formed, showing a strong dependence on the treatment duration.…”
Section: Resistive Switching Mechanismmentioning
confidence: 99%
“…[1] More intriguingly, a significant amount of energy is wasted in transferring the data control of the stochastic filament formation. [9,[17][18][19][20][21][22] However, such double-layered structure usually requires two different oxide materials to be deposited via multistep processing, such as physical sputtering and atomic layer deposition (ALD) at the expense of a thick RS layer, low on/off ratio, and/or large forming voltage. [9,[20][21][22] By far, double-layered RS medium based on oxides has been limited to a thickness above 6 nm, placing a constraint on its scalability limit for further performance enhancement.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When a negative voltage of sufficient magnitude is applied to the TE, the device reaches the LRS because the V N move back toward the active interface, restoring the metal-rich character of the CF at this interface and widening the CF (see Section S1). However, in filamentary VCM devices a much larger window between LRS and HRS is typically experienced. , The small memory window in the present case could be explained by an extremely narrow gap or by the presence of a significant amount of V N in the gap region in HRS. This could be caused by an insufficiently abrupt I cc for limiting the fast thermal runaway during this process …”
mentioning
confidence: 63%